Preliminary investigation of multiple resistance in goosegrass (Eleusine indica) to premix of diuron and MSMA, glyphosate, clethodim, quizalofop in Malaysia - Azlan, Muhammad Izwan; Kamarudin, Khairun Nisa; Chuah, Tse-Seng (Advances in Weed Science, 2025)
Background The primary challenge in Malaysian vegetable farms is the herbicide resistance in E. indica. Objective: This study aimed to assess herbicide resistance in E. indica biotypes on a cucumber farm in Penang, Malaysia.Methods Seedlings of the putative resistant and susceptible biotypes were propagated and transferred into seedling trays containing peat moss. The seedlings were subjected to premix of diuron and MSMA, glufosinate, glyphosate, oxyfluorfen, napropamide, quiazlofop and clethodim treatments at the three-to-four-leaf stage.Results Dose-response tests showed that the resistant biotype was 15-fold, 12-fold, 80-fold, and 2-fold more resistant to glyphosate, clethodim, quizalofop, and the diuron plus MSMA premix, respectively, compared to the susceptible biotype based on herbicide rates which caused 50% reduction in shoot dry weight. However, both biotypes were susceptible to glufosinate, oxyfluorfen and napropamide treatments.Conclusions The findings have confirmed multiple herbicide resistance in goosegrass to glyphosate, clethodim, quizalofop, and premix of diuron and MSMA.